Dramatic response of advanced pulmonary sarcomatoid carcinoma to tislelizumab combined with anlotinib: a case report - Ranran Li; Xiliang Di; Yuan Li; Hao Li; Chonghua Liu (Frontiers in Oncology)
Pulmonary sarcomatoid carcinoma (PSC) is a scarce pathologic type of lung cancer of non-small cell lung cancer (NSCLC) that exhibits resistance to conventional chemotherapy and radiotherapy, resulting in a poor prognosis. Herein, a 67-year-old man was admitted to the hospital in January 2022 with a diagnosis of PSC for over 6 months and a newly discovered brain metastasis for 4 days. He had previously undergone two unsuccessful chemotherapy regimens: bevacizumab combined with pemetrexed and loplatin, and albumin-bound paclitaxel combined with loplatin. Radiotherapy was performed for the brain and skull metastases, followed by treatment with tislelizumab combined with anlotinib, a programmed cell death protein 1 (PD-1) inhibitor with anti angiogenic drug, respectfully. The patient initially received nine cycles of treatment with tislelizumab and anlotinib, resulting in a significant shrinkage of the lung tumor. Subsequently, anlotinib was discontinued due to bleeding in the brain metastasis, and the patient received two additional cycles of tislelizumab. Following improvement in the hemorrhage from brain metastasis, the patient received two cycles of treatment with tislelizumab and anlotinib. Treatment was subsequently interrupted for 1 month due to the coronavirus disease 2019 (COVID-19) pandemic, which then resumed with two additional cycles of tislelizumab and anlotinib. Finally, the patient refused to continue treatment due to the progression of the brain metastasis and economic conditions, despite the stable condition. At this point, the patient has achieved over a year of progression-free survival, with overall survival exceeding 39 months. This case illustrates the efficacy and safety of combining antitumor immunotherapy with anlotinib, a targeted anti-angiogenic therapy.